(untitled) (Proceeding of Dakwah Saizu International Conference, 2023)
Broken home is a family state that does not lead to harmony, keruru, and family comfort, which is caused by several reasons such as divorce, death of one of the parents, or separation of others, and causing the family to be separated. The impact of Broken Home is one of them, which is unstable emotion, especially for his parents, which raises an impingement of emotions by verbal abuse to his child. Therefore, selfefficacy is needed to overcome this problem. This study aims to describe self-efficacy 3 student guidance and Islamic counseling in overcoming verbal abuse in the Broken Home family. This study uses a type of qualitative research with a descriptive approach. The techniques used in data collection are observation techniques, in-depth interviews and documentation. Data analysis uses data reduction steps, data presentation, and conclusion drawings. Verbal forms of abuse carried out by families of the three informants were generally intimidation, reduced self-esteem, and the habit of crawling children. The actions of the third self-efficacy informant in overcoming verbal abuse, namely generally by confiding in trusted people, avoiding, and correcting errors. The results of the study illustrate that the three informants had good self-efficacy in overcoming forms of verbal abuse from their families.